Sistem Informasi Komoditi Nelayan Desa Pusong Lama Kota Lhokseumawe - Amrullah, Novia Hasdyna, Rahmat, Putri Nahrisa (Jurnal Elektronika dan Teknologi Informasi, 2022)
Data on fishery resources and the environment in Lhokseumawe City, Desa Pusong Lama have not been processed and compiled properly which results in less or slow information received by actors in the fisheries system, as well as the use of technology that has not been maximized in data processing. This study builds an information system for fishery products in Pusong Lama Village, Lhokseumawe City so that the delivery of information is better and can be accessed quickly by all actors. The fishery system can make it easier to make a decision to build a business in the fisheries sector. With this information system, it can provide convenience to users in processing and searching fishery resource data, the environment and fisheries technology in Pusong Lama Village. The web-based information system is built using the PHP programming language.